Intraoperative fluorescent spectroscopy and photodynamic therapy of recurrent pelvis minor tumors with local radiation damage - L. A. Vasilev; N. S. Panov; V. N. Kapinus; M. A. Kaplan; I. P. Kostyuk; A. D. Kaprin (Biomedical Photonics, 2018)
This work presents the results of performing intraoperative photodynamic therapy (IOPDT) on 22 patients with recurrent pelvic tumors(cervical cancer – in 18 patients, cancer of the corpus uteri – in 3 patients, cancer of the anal canal – in 1 patient). Prior to the PDT procedure, the patients were injected with photolon photosensitizer (PS) at a dose of 1.0–1.1 mg/kg. After the injection of PS, local fluorescence spectroscopy of tumor lesions was performed to determine the accumulation of drug in various areas of tumors and healthy tissue. Intraoperative laser irradiation was carried out 3–5 hours after the photolon injection with light at 662 nm wavelength using "Latus-2" laser device with a power density of 140 mW/cm2 and the density of light energy of 40–60 J/cm2, the number of irradiation fields was 3–5 depending on the anatomical features.The follow-up period after surgical treatment combined with PDT was from 6 to 24 months. Analyzing the immediate results of the treatment, there were no undesirable events or increase in the number of postoperative complications compared to patients treated without IOPDT. Were registered: transient increase in ALT and AST levels – in 5 patients (13.6%), reduction of oxygenation during anesthesia – in 20 (90.9%), transient fevers in the postoperative period – in 7 (31.8%).It was noted that IOPDT with photolon drug, while slightly extending the time of the operation, is well tolerated by patients and does not lead to an increase in the number of early postoperative complications or the length of hospitalization.